Asymmetric Rubottom‐Type Oxidation Catalyzed by Chiral Calcium Phosphates. Issue 10 (20th January 2023) - He, Hualing; Tummalapalli, K. S. Satyanarayana; Zhu, Linfei; Chen, Minglei; Krishnamurthy, Suvratha; Antilla, Jon C.
Abstract: A highly efficient catalytic asymmetric Rubottom‐type oxidation is described. Using meta ‐chloroperbenzoic acid ( m ‐CPBA) as the oxidant and chiral calcium phosphate as the catalyst, the facile transformation enables direct hydroxylation of N ‐Boc oxindoles and β‐ketoesters in high yields (up to 99 %) and in a highly enantioenriched fashion (up to >99 % ee ). The application of the established method was demonstrated by the synthesis of a pharmaceutically important 3‐hydroxyoxindole with excellent enantiocontrol. Abstract : A highly efficient catalytic asymmetric Rubottom‐type oxidation is described. Using meta ‐chloroperbenzoic acid ( m ‐CPBA) as the oxidant and chiral calcium phosphate as the catalyst, the facile transformation enables direct hydroxylation of N ‐Boc oxindoles and β‐ketoesters in high yields (up to 99 %) and in a highly enantioenriched fashion (up to >99 % ee ).